Pakistan's ration system: Distribution of costs and benefits - Rogers, Beatrice (International Food Policy Research Institute, 1988)
Pakistan's ration system was established in 1942 to deal with shortages of basic goods caused by wartime disruption in supply. At that time, the ration shops handled wheat and sugar, tea, matches, kerosene, yarn, and cotton cloth. After partition, the system was continued to control hoarding and profiteering of scarce goods. All trade in wheat was rationed and controlled by the government until the 1960s when, as a result of several years of favorable weather, supplies became plentiful. Rationing was abolished, but the shops continued to sell atta (whole wheat flour), which the government obtained through its guaranteed price support scheme, with no limitation on quantity.